2020
DOI: 10.3390/v12040375
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis in a Mammalian Cell Line Reveals that PLK2 Is Involved in Avian Metapneumovirus Type C (aMPV/C)-Induced Apoptosis

Abstract: Avian metapneumovirus subtype C (aMPV/C) causes an acute respiratory disease that has caused serious economic losses in the Chinese poultry industry. In the present study, we first explored the protein profile in aMPV/C-infected Vero cells using iTRAQ quantitative proteomics. A total of 921 of 7034 proteins were identified as significantly altered by aMPV/C infection. Three selected proteins were confirmed by Western blot analysis. Bioinformatics GO analysis revealed multiple signaling pathways involving cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Numerous studies have shown that viruses replicate in host cells by utilizing the host signal pathways and/or proteins. A recent report of iTRAQ quantitative proteomics showed that multiple signaling pathways, such as mTOR, MAPK, and p53, participate in aMPV/C replication [ 9 ]. In this study, a series of experiments were carried out to determine the influence of NCL on viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have shown that viruses replicate in host cells by utilizing the host signal pathways and/or proteins. A recent report of iTRAQ quantitative proteomics showed that multiple signaling pathways, such as mTOR, MAPK, and p53, participate in aMPV/C replication [ 9 ]. In this study, a series of experiments were carried out to determine the influence of NCL on viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of aMPV/C infection in chicken. It has been reported that aMPV/C participated in the regulation of multiple biological processes for viral replication [8,9]. Nucleolin (NCL), a highly conserved protein during evolution that is located in the nucleolus [10][11][12], participates in a variety of biological processes, such as chromatin organization and stability, ribosome biogenesis, apoptosis regulation, and stress response [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, avian metapneumovirus subtype C (aMPV/C) infection leads to upregulation of PLK2 in mammalian cells. Inhibition of PLK2 could reduce ROS production and p53-dependant apoptosis induced by aMPV/C, and decrease the virus release, suggesting that the high expression of PLK2 is associated with aMPV/C-induced apoptosis and viral replication ( 89 ). Contrasting to its family members, PLK2 is poorly studied in viral infection, and the exact role and mechanism remain unclear.…”
Section: Role Of Plk2 In Basic Pathophysiological Processesmentioning
confidence: 99%